2019
DOI: 10.14309/ajg.0000000000000398
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Adverse Impact of Hepatotoxicity due to Immune Checkpoint Inhibitors

Abstract: INTRODUCTION: We conducted this study to characterize the incidence, clinical features, treatment, and outcomes of immune checkpoint inhibitor (ICI) hepatotoxicity. METHODS: Patients who received ICIs (with either single-agent or combination regimens) from January 1, 2010, to March 31, 2018, were identified. Hepatotoxicity was defined as alanine aminotransferase (ALT) >5 times the upper limit of normal (ULN), in the absence of an alternate cause, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 24 publications
3
67
0
Order By: Relevance
“…A retrospective study conducted at MD Anderson Cancer Center on 5762 patients receiving ICIs found that 2% developed hepatotoxicity (especially in combination treatment), of whom 69% permanently discontinued relevant ICIs; 10 of 67 patients receiving corticosteroids had recurrent hepatotoxicity after the corticosteroid taper, and 31 patients resumed ICIs after transaminases improvement, 8 of whom (26%) developed recurrent hepatotoxicity. Notably, no differences emerged in terms of characteristics of liver injury, response to corticosteroids, and outcomes between individuals with and without possible pre-existing liver diseases [88].…”
Section: What's Missing: Managementmentioning
confidence: 96%
“…A retrospective study conducted at MD Anderson Cancer Center on 5762 patients receiving ICIs found that 2% developed hepatotoxicity (especially in combination treatment), of whom 69% permanently discontinued relevant ICIs; 10 of 67 patients receiving corticosteroids had recurrent hepatotoxicity after the corticosteroid taper, and 31 patients resumed ICIs after transaminases improvement, 8 of whom (26%) developed recurrent hepatotoxicity. Notably, no differences emerged in terms of characteristics of liver injury, response to corticosteroids, and outcomes between individuals with and without possible pre-existing liver diseases [88].…”
Section: What's Missing: Managementmentioning
confidence: 96%
“…BILIARY TRACT CPI therapy-induced liver injury is reported in about 2% to 10% patients with CPI therapy. 45,47 The injury occurs between approximately 1 to 3 months with anti-PD-1/PD-L1 agents, and between about 3 to 9 weeks with anti-CTLA-4 agents after initiation of therapy. 45,48,49 The injury may vary with the type of CPI therapy agents used.…”
Section: Patterns Of Injury To the Liver Andmentioning
confidence: 99%
“…Overall incidence of all grade elevated ALT from anti-PD-1 or anti-PD-L1 in patients with primary liver cancer was 14 3A and Supplemental Figure S3). Interestingly, the incidence of allgrade elevated ALT, AST and bilirubin, and hepatobiliary disorders was statistically higher in primary liver cancer versus other cancer types (p<0.001, Table 3), but not the elevation of ALP/GGT and ir-hepatitis.…”
Section: Individual All-grade Hepatoxicity In Primary Liver Cancers Compared To Other Cancer Typesmentioning
confidence: 99%
“…Clinically, hepatotoxicity can present with a range findings, from mild elevation of liver enzymes to hepatobiliary disorders like autoimmune hepatitis, cholangitis, jaundice and liver failure (10,11). Currently, there are several meta-analyses that have evaluated hepatotoxicity from ICIs and found a general incidence of 2-30% (7,8,(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%